POLISI PENTADBIRAN DAN PENGURUSAN TANAH: ANALISIS PERBANDINGAN ANTARA KANUN TANAH NEGARA DAN HUKUM ISLAM - Abdullah, Naziruddin (Jurnal Syariah, 2019)
This article is written with a two-fold plan. First, it explains and analyses the issue of land management and administration, taking Malaysia as a case study. Second, a comparison is made between the two most commonly debated ways of managing and administrating land in Malaysia, i.e., the Islamic land laws vis-a-vis the British-based land laws. While the issues of land management and administration that were raised and then opined by the early Muslim scholars like Abu Yusuf, Mawardi and Abu Ya 'la are taken to represent the Islamic standpoint, the Kanun Tanah Negara, which to a large extent is an offshoot of the Torrens System, is taken to represent the British-based land laws. Having examined the two land laws it is found that there is no substantial discrepancy between them. In fact, the remaining differences can easily and readily be rectified if they are brought to the attention of the members of parliament and state representatives whose responsibility is to debate, harmonise, and pass the refined land laws, as mandated by their respective constituents.